Epidemio-Clinical Profile of Acute Diarrhea in Children From 0 To 5 Years and Prevalence of Rotavirus Before and After the Introduction of the Rotasiil Vaccine in the Democratic Republic of Congo. - Freddy, Mboko Byamungu; Loukia, Paizanos Aketi; Joseph, Diayisu Shiku; Joëlle, Nzuzi Bemba; Rosette, Kevaani Lepira; Irène, Kifutu Matula; Éric, Tshitona Kaluli (Journal of Diseases, 2023)
Introduction Acute diarrhea remains one of the major health problems in developing countries. According to the WHO, rotavirus contributes to approximately 40% hospitalizations and is the leading cause of severe diarrhea in children 0-5 years old. The objective was to determine the prevalence of rotavirus and the sociodemographic and clinical profile among children with diarrhea in 4 hospitals in the DRC. Methods This study is documentary, retrospective and analytical taking two periods, before and after introduction of the vaccine, i.e. January 2017 to December 2018 and January 2020 to December 2021 in 4 hospitals, i.e. 2 in Kinshasa and 2 in Lubumbashi. Results Total 1872 children, 924 (49.4%) of whom were enrolled before the introduction of the vaccine and 948 (50.6%) after. Only 1737 had performed serology, of which 875 (50.4%) were rotavirus positive and 862 (49.6%) were negative. Positive results, a reduction of 30.6% is noted since the introduction of the vaccine. The predominant age range was 6 to 11 months. The male gender was predominant at 56.7%. Diarrhea was found in 88.5%, vomiting in 73.7% and fever in 73.9%. Before vaccination, the risk was more: 11 times to have diarrhea, 9-10 times the frequency between 3-10 times a day, 9 times vomiting, 2 times fever and 2 times to have a positive result. Conclusion From this study, we note a reduction frequency due to diarrhea unlike previous years, probably attributable to the vaccine.
Keywords: Diarrhea; after and before vaccine Rotavirus; Kinshasa; DRC.